Bang the drum slowly [videorecording (DVD)] - Hancock, John, 1939-; De Niro, Robert; Moriarty, Michael, 1941-; Gardenia, Vincent; Foster, Phil, 1914-1985; MacRae, Heather, 1946-; Aiello, Danny, 1933-2019-; Harris, Mark, 1922-2007 (Paramount, 2003)
An unlikely friendship ignites between two baseball players. One is the team's ace pitcher and social charmer; the other is the catcher, a farm boy from Georgia who lacks sophistication. During their last season together, the two men grow in manhood and respect for themselves and each other.